MANAJEMEN RISIKO BENCANA BANJIR DI KOTA CIREBON - Mohammad Rivaldy; Sobar Sutisna; Robertus Anugerah Purwoko Putro; Syamsul Maarif (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2025)
FLOOD DISASTER RISK MANAGEMENT IN CIREBON CITY In recent years, Cirebon City has experienced an increasing trend in the frequency and intensity of flood events. As a result, the community has experienced large material and immaterial losses, as well as disruption of economic and social activities. This condition requires a response strategy and measurable in disaster management. This study aims to analyze the implementation of flood disaster risk management that has been carried out by the Cirebon City Regional Government. By combining interactive data analysis and a descriptive approach, this study shows that the Cirebon City Regional Disaster Management Agency plays an important role in reducing the risk of flood disasters in urban areas, which are divided into three stages: prevention, mitigation, and preparedness. Although efforts to reduce the risk of flood disasters continue to be made, this study emphasizes the importance of evaluating and improving the sustainability of policies, programs, activities, and sub-activities that have been designed. This periodic review needs to be carried out to ensure that the performance of the indicators that have been set can be achieved optimally, so that Cirebon City can be more resilient in facing future flood disasters.